(3QhVI GdCdHGH hJMaI GdCMHGH hHZjI GdWdGH hfNHI GdCMSGH deYQaI GdCfSGHs - (3GHf GdeDjO , eMeO Hf YHO Gddg Hf Ydj Hf GdMSjf Hf YR GdOjf, CHh YdGeI,J (B1031 (3g` s ((3eMeO Hf CMeO Hf GdeaVd Hf EHQGgje Hf Ydi Hf CejQ GdeDefjf jMji TQa GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdSehGJ hGdCQV s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B226s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B170 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs